A COMPARATIVE STUDY BETWEEN COLONIAL WOMEN WRITERS IN SARAWAK IN TWO DIFFERENT TIME PERIOD - Muhammad, Nur Farhana; Fadzli, Mursyidah Amani Mohamed (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This article examines the colonial-era writings of two Englishwomen, Margaret and Sylvia Brooke, through a comparative analysis of their respective portrayals of life as consorts to the ‘White Rajahs’ of Sarawak. Margaret, wife of Charles Brooke (the second Rajah), and Sylvia, wife of his son Vyner (the third and final Rajah), occupied similar roles within the Brooke dynasty but approached their experiences from markedly different personal and historical vantage points. Their memoirs, shaped by generational shifts and contrasting temperaments, offer divergent narratives rather than a unified perspective. The relationship between the two women appears to have been distant, even strained, and this tension is mirrored in their writings. The concurrent publication of certain volumes of their memoirs may have reinforced a sense of literary rivalry, especially for Sylvia. Margaret’s tone is measured and discreet, while Sylvia adopts a more assertive, self-promoting stance, reflecting the broader cultural and media shifts of the early 20th century. These differences also manifest in their representations of colonial knowledge. Margaret displays a sustained interest in the indigenous communities of Sarawak, signalling an engagement with local contexts. In contrast, Sylvia projects a louder, assertive image, consciously cultivating her public persona as the ‘Queen of the Headhunters.’ Rather than subsuming both figures under broad postcolonial-feminist notions of ambivalence, this study argues for a more nuanced reading of colonial women’s writing, one that recognises the intra-gender and intergenerational conflicts embedded within imperial narratives. The comparison underscores the need to move beyond homogenised interpretations of white women’s roles in empire, attending instead to the complexities of individuality, authorship, and power in colonial settings.